A Translation Shift Analysis Of Noun PhraseIn Subtitling Of Ice Age 4 Movie - Sunarto, Edy, Dr. Dwi Haryanti, M.Hum, Drs. Sigit Haryanto, M.Hum (2015)
This research aims to identify the translation shifts of noun phrase and to describe the equivalence of noun phrase's meaning found in the film entitled Ice Age 4 movie. The data in this research are English and Indonesian movie subtitling. The data source was in Ice Age 4 movie subtitle containing noun phrase. The type of this research is descriptive qualitative research. The writer uses documentation technique to collect the data. The result of this research shows that first, there are four types of translation shift of noun phrase, i.e. First, from 403 data, there are 197 data or 48,9% belong to level shift of noun phrase, 157 data or 39% belong to structure shift of noun phrase, 18 data or 4,5% belong to translation shift of noun phrase to another phrase, and 31 data or 7,6% belong to intra-system shift of noun phrase. Second, there are 390 data or 97% belong to equivalent translation and 13 data or 3% belong to not equivalent translation. Key word: subtitling, translation shift of noun phrase, equivalent.